Tailoring tricolor structure of magnetic topological insulator for robust axion insulator - Mogi, M; Kawamura, M; Tsukazaki, A; Yoshimi, R; Takahashi, K S; Kawasaki, M; Tokura, Y (arXiv.org, 2017)
Exploration of novel electromagnetic phenomena is a subject of great interest in topological quantum materials. One of the unprecedented effects to be experimentally verified is topological magnetoelectric (TME) effect originating from an unusual coupling of electric and magnetic fields in materials. A magnetic heterostructure of topological insulator (TI) hosts such an exotic magnetoelectric coupling and can be expected to realize the TME effect as an axion insulator. Here we designed a magnetic TI with tricolor structure where a non-magnetic layer of (Bi, Sb)2Te3 is sandwiched by a soft ferromagnetic Cr-doped (Bi, Sb)2Te3 and a hard ferromagnetic V-doped (Bi, Sb)2Te3. Accompanied by the quantum anomalous Hall (QAH) effect, we observe zero Hall conductivity plateaus, which are a hallmark of the axion insulator state, in a wide range of magnetic field between the coercive fields of Cr- and V-doped layers. The resistance of the axion insulator state reaches as high as 10^9 ohm, leading to a gigantic magnetoresistance ratio exceeding 10,000,000% upon the transition from the QAH state. The tricolor structure of TI may not only be an ideal arena for the topologically distinct phenomena, but also provide magnetoresistive applications for advancing dissipationless topological electronics.